Bank Competition, Financing Obstacles, and Access to Credit - Beck, Thorsten; Demirguc-Kunt, Asli; Maksimovic, Vojislav (World Bank, Washington, DC, 2014)
Theory makes ambiguous predictions about the effects of bank concentration on access to external finance. Using a unique data base for 74 countries of financing obstacles and financing patterns for firms of small, medium, and large size, the authors assess the effects of banking market structure on financing obstacles and the access of firms to bank finance. The authors find that bank concentration increases financing obstacles and decreases the likelihood of receiving bank finance, with the impact decreasing in size. The relation of bank concentration and financing obstacles is dampened in countries with well developed institutions, higher levels of economic and financial development, and a larger share of foreign-owned banks. The effect is exacerbated by more restrictions on banks' activities, more government interference in the banking sector, and a larger share of government-owned banks. Finally, it is possible to alleviate the negative impact of bank concentration on access to finance by reducing activity restrictions.